INVESTIGATION OF THE EFFECT OF PARTICLE SIZE ON GROUNDNUT-OIL SOLVENT EXTRACTION - Manyele, S. V.; Kahemela, I. F. (Tanzania Journal of Engineering and Technology, 2018)
An investigation of the effect of particle size on the performance of vegetable oil recovery by solvent extraction is reported. Experiments were conducted using soxhlet extractor, groundnuts and n-hexane. Samples were grouped into mean particle sizes of 0.25, 0.75, 1.3, 3.3, and 7.5 mm using standard sieves. The effect of particle size was studied for extraction time intervals of 1, 2, 3, 4, 5 and 8 hours. The oil yield, oil recovered per kg solvent used, kg solvent lost per unit time, and the rate of extraction (kg oil recovered per hour) decreased with increasing particle size. Meanwhile, the percent of solvent recovered, the ratio of oil recovered to the total volatile matter driven off and the kg solvent lost per kg oil recovered, increased with increasing particle size. Based on the normalization of averaged extraction-parameters, a mean particle size of 3.3 mm was observed to be the optimum size.